Three-dimensional Ge/GeO2 shell-encapsulated Nb2O5 nanoparticle assemblies for high-performance lithium-ion battery anodes. (20th April 2020) - Kim, Kyungbae; Seo, Hyungeun; Kim, Han-Seul; Lee, Hyun Seung; Kim, Jae-Hun
Abstract: We report an efficient nanostructure of three-dimensional germanium/germanium dioxide (Ge/GeO2 ) shell-encapsulated niobium pentoxide (Nb2 O5 ) nanoparticle assemblies for high-performance Li storage anode materials. The Ge/GeO2 -encapsulated Nb2 O5 nanoassemblies are prepared via a simple solvothermal synthesis method. The Ge/GeO2 layer binds the surfaces and interfaces of the interconnected Nb2 O5 nanoparticle assemblies, presenting as dense and uniform microspheres. The tightly bound Ge/GeO2 layer interconnects the nanoassemblies to provide high capacity and a pathway for Li + and electron transport. Via the Nb2 O5 assemblies, fast Li + transport kinetics are secured using a pseudocapacitive reaction mechanism during Li insertion and extraction, while Ge nanoparticles provide the high specific capacity. As a result, the Ge/GeO2 -encapsulated Nb2 O5 microspheres deliver a greatly enhanced reversible capacity of 800 mA h g −1 and excellent high-rate capability. The superior high-performance in Ge/GeO2 -encapsulated Nb2 O5 microspheres arises from a synergetic effect between the interconnected microstructure and the highly reversible GeO2 phase. The encapsulated interconnection material design concept allows control of the Ge-based electrode materials composition making it ideal for fabrication of high-performance electrodes in Li-ion batteries. Graphical abstract: Image 1 Highlights: Three-dimensional Ge/GeO2 shell-encapsulated Nb2 O5 nanoparticle assemblies were prepared. Newly designed nanostructure was effective for fast reversible Li storage. Li storage mechanism in the structure was demonstrated using various analytical tools. The material design concept can be used for various applications.